A ntibacterial Activity of Blue Pea Flower (Clitoria ternatea) Acetone Extract Against Propionibacterium acnes and Citrobacter freundii Bacteria - Tita Juwitaningsih; Hidayani (Indonesian Journal of Chemical Science and Technology (IJCST), 2026)
This study aims to determine the antibacterial activity of acetone extract of blue pea flower (C. ternatea) against P. acne and C. freundii bacteria and to identify the secondary metabolites contained in acetone extract of blue pea flower (C. ternatea). Blue pea flower was extracted using the maceration method with acetone solvent. Preliminary antibacterial activity tests were conducted using the disk diffusion method. This was followed by the determination of the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values. Phytochemical screening tests were conducted using test tubes. The effectiveness of the acetone extract of butterfly pea flower showed antibacterial activity against P. acne bacteria with a value of 34% and against C. freundii bacteria with a value of 22.4%. The MIC and MBC values against P. acne and C. freundii bacteria were 1250 µg/mL and >5000 µg/mL, respectively. The phytochemical screening test results showed that the acetone extract of butterfly pea flower contained flavonoids, saponins, tannins, and steroids.